Attenuation Model of Wireless Sensor Network for Large-Scale Farmland Environment - Wu Huarui; Zhao Chunjiang; Zhu Li (Institute of Advanced Engineering and Science, 2013)
The transmission characteristics of wireless sensor network nodes for large-scale farmland are influenced by factors such as farmland terrain environment, planting density and height. The vegetation canopy can absorb, scatter, and block RF signals, leading to large attenuation of signal strength and significant differences in link quality on the receiving end, which in turn affects the monitoring quality. The dynamic relationships between radio signal transmission, plant height, group range, and crop growth stages are identified through the analysis of summer corn perceptual information path loss at different growth stages. The gradual RSSI attenuation model of wireless sensor network for large-scale farmland environment is established. Research shows that during the corn tassel and seed-filling periods, the RSSI attenuation is most serious and the perception range reaches the minimum value when antenna height falls in the range of 0.5 meter to 1.7 meters. Through the model we can predict the intensity and perception range of the received wireless signals of summer corn on various perception levels at different growth stages. This model serves as the theoretical basis for the deployment of wireless sensor network nodes for large-scale farmland, aiming to achieve maximum monitoring range at minimum equipment cost. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1981